Scaling up of in vitro micropropagation of Musa spp. Mysore - AAB, cv. 'Embul' - Samangika, A.G.G. (My University, 2010)
In vitro micropropagation technology through shoot tip culture technique of in vitro micropropagationof Musa spp. Mysore-AAB,cv. 'Embul' banana is well practiced in the country.Howevera few steps need to be further improved. One main constraint is the time taken for culture initiation. Therefore it is necessary to develop the technology further. The present study reports a further development of the technology by improving several conditions to enhance the rate of culture initiation/greening, minimize the time taken for bud break and to produce maximum number of buds within a short period of time while maintainingquality, quantity, continuity and cost effectiveness of the already available technology. A protocolwas developed for the form of shoot tip (explant) by utilizing Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurine (2.25 mg/L) and indole-3-aceticacid (0.175 mg/L). Three shoot forms (intact form, with two incisionsat the top of the tip and longitudinallyhalved through apical meristem)were tested. Longitudinally halved shoot tips through apical meristem induced the maximum percentage of explants (66.67 %) and produced the highest number of shoots per explant (2) in two months (8-9 weeks). The culture initiation/greeningof explants has been rapid and majority of cultures were initiated at 3 -6 days after inoculation. The media protocol was also modified by supplementing MS medium with 6-BAP(2.25mg/L),IAA(0.175mg/L) and adenine sulphate(1.0 - 4.0 mg/L) and the medium incorporated with adenine sulphate (2.0 mg/L) induced the highest number of explants leading to bud break (33.33 %). The combinedeffect of the adenine sulphate and shoot tip form was also studied. Rapid culture initiation/greeningfrom 3-5 days was shown by 2.0 mg/L adenine sulphate with longitudinallyhalved shoot tips through apical meristem.Furthermore,62.50 % of explants were induced leading to early bud break (from the third week after inoculation) and the maximumnumberof shoots(4)was producedby the same combination. The study revealed that the already practicing technology at commercial level could be further developed by using longitudinally halved shoot tips with 2.0 mg/L adenine sulphate added to . the culture initiation medium.